The Combat Sports in Physical Education Classes – A Basic Perspective - Figueiredo, Abel (2010)
Combat Sports (CS) are not as traditional to Physical Education (PE) classes as collective and individual sports. They divide many teachers. Some of us accept them, other ones defend them, and some others of us repeal them from PE classes. In this paper we assume that Sport and PE are not neutral. They are context processes that depend from various circumstances for stimulation of Human Motricy (HM), even if there are many people that perception them as “good” by self existence. We will present an approach, for reflexive purposes, about exercises or tasks linked with CS in a not so institutionalized perspective as traditional sports.